Lean healthcare : aplicação do diagrama de espaguete em uma unidade de emergência - Deguirmendjian, Samira Candalaft (2016)
Every day we are faced with constant waste and activities that do not add any value in hospitals. Aspects related to communication, unnecessary movement of professionals, patients, materials and information, useless protocols although well written are increasingly observed in health services. For improvements related to handling flow and continuous elimination of waste and activities that do not add value in the hospital, this study aimed to assess the implementation of spaghetti diagram tool in an emergency room of a small hospital in the state of São Paulo. The healthcare lean methodology and spaghetti diagram tool was used. It was identified the current situation and opportunities for improvement, relating to proposition good spaghetti diagram practices in hospitals. The main movement of wastes were mentioned and it was noted that the application of the tool was successful. The importance of the method for reducing the waste stream related to movement flow in a hospital environment has been proved. It is expected that the flow of tasks become efficient, always seeking less time to perform activities using less effort, less cost and reducing the waiting time of the patients in the unit by reorganizing the movement flow in the workplace.